EMPOWERING GOMBENGSARI COFFEE FARMERS TOWARDS SUSTAINABLE AGROTOURISM - Nurul Dwi Novikarumsari; Sri Subekti (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
This study aims to analyze the empowerment of coffee farmers in Gombengsari Village, Kalipuro District, Banyuwangi Regency in supporting sustainable agro-tourism. This study used a qualitative approach with data collection methods from in-depth interviews, and literature review. The results showed that the empowerment of Gombengsari coffee farmers involved various stakeholder roles, the goals are farmers will have a full level of empowerment.